Essential oils of Lippia sidoides and Mentha piperita against monogenean parasites and their influence on the hematology of Nile tilapia - de Oliveira Hashimoto, Gabriela Sayuri; Neto, Fausto Marinho [UNESP]; Ruiz, Maria Luiza; Acchile, Monyele; Chagas, Edsandra Campos; Chaves, Francisco Célio Maia; Martins, Maurício Laterça (Elsevier, 2016)
This study evaluated the use of therapeutic baths containing essential oils of Lippia sidoides (pepper rosemary) and Mentha piperita (peppermint) on the hematological parameters of Nile tilapia parasitized by the monogeneans Cichlidogyrus tilapiae, Cichlidogyrus thurstonae, Cichlidogyrus halli, and Scutogyrus longicornis. A total of 320 juvenile fish were distributed into 16 tanks of capacity 100L (20 fish per tank), divided into 4 treatments in quadruplicates: fish exposed to a bath of L. sidoides at 20mgL-1; fish exposed to M. piperita at 40mgL-1; fish exposed only to a water bath; and fish exposed to water+DMSO (dimethyl sulfoxide) bath. The fish were subjected to 3 baths for 10min, at intervals of 24h between treatments. After the third bath, parasitological and hematological analyses were performed. The parasite prevalence in fish treated with essential oils was seen to have decreased by 70%. The efficacy attained among fish treated with L. sidoides, in comparison with control water and water+DMSO, was 1.96% and 14.16%, respectively; and among fish treated with M. piperita, it was 33.33% and 41.63%, respectively. The total numbers of red blood cells (RBC) and thrombocytes were lower in fish treated with L. sidoides. Glucose concentration and neutrophil count were significantly higher in fish treated with L. sidoides. Because of the efficacy and positive hematological results, we suggest that baths of M. piperita at 40mgL-1 should be used as anthelmintic action. Statement of relevance: Authors believe on the use of essential oils to treat ectoparasites of cultured fish and consequently no damages for hematological profile of Nile tilapia were found.
Keywords: Anti-parasitic; Blood; Fish; Peppermint; Phytotherapy; Rosemary pepper